2017
DOI: 10.3389/fnins.2017.00610
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DmMANF in Glial Cells Results in Neurodegeneration and Affects Sleep and Lifespan in Drosophila melanogaster

Abstract: In Drosophila melanogaster, mesencephalic astrocyte-derived neurotrophic factor (DmMANF) is an evolutionarily conserved ortholog of mammalian MANF and cerebral dopamine neurotrophic factor (CDNF), which have been shown to promote the survival of dopaminergic neurons in the brain. We observed especially high levels of DmMANF in the visual system of Drosophila, particularly in the first optic neuropil (lamina). In the lamina, DmMANF was found in glial cells (surface and epithelial glia), photoreceptors and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…In neurons, on the other hand, it can be found only in the somata (Stratoulias and Heino, 2015a ). In our recent study (Walkowicz et al, 2017 ) we found that DmMANF is strongly expressed in the epithelial glial cells (EGl) of the first visual neuropil (the lamina). Here we show, that it is also clearly present in the cell bodies and, most importantly, the processes of EnGl (Figures 6C,D” ).…”
Section: Discussionmentioning
confidence: 90%
“…In neurons, on the other hand, it can be found only in the somata (Stratoulias and Heino, 2015a ). In our recent study (Walkowicz et al, 2017 ) we found that DmMANF is strongly expressed in the epithelial glial cells (EGl) of the first visual neuropil (the lamina). Here we show, that it is also clearly present in the cell bodies and, most importantly, the processes of EnGl (Figures 6C,D” ).…”
Section: Discussionmentioning
confidence: 90%
“…However, one should keep in mind that repo expression does not necessarily label all glial cells in the nervous system. The midline glia, which are a small set of specialized wrapping glia in the CNS, as well as the Mesencephalic astrocyte‐derived neurotrophic factor (MANF) expressing cells which might correspond to microglial‐like cells do not express Repo (Halter et al, ; Klaes et al, ; Palgi et al, ; Stratoulias & Heino, ; Walkowicz et al, ; Xiong et al, ). Likewise, the cone cells of the adult Drosophila compound eye, which based on molecular signatures show a remarkable homology to Drosophila and vertebrate glia only transiently express Repo (Charlton‐Perkins, Sendler, Buschbeck, & Cook, ).…”
Section: Drosophila Gliogenesismentioning
confidence: 99%
“…However, one should keep in mind that repo expression does not necessarily label all glial cells in the nervous system. The midline glia, which are a small set of specialized wrapping glia in the CNS, as well as the Mesencephalic astrocyte-derived neurotrophic factor (MANF) expressing cells which might correspond to microglial-like cells do not express Repo (Halter et al, 1995;Klaes et al, 1994;Palgi et al, 2009;Stratoulias & Heino, 2015;Walkowicz et al, 2017;Xiong et al, 1994).…”
Section: Drosophila Gliogenesismentioning
confidence: 99%
“…in particular in the lamina epithelial glial cells, which exhibits holes and/or tightly packed membranes and also a decrease of capitate projections in the cartridges (Walkowicz et al, 2017). In glial cells, DmMANF is also involved in controlling the levels of dopamine and other neurotransmitters responsible for Drosophila behaviour.…”
Section: Compound Eyesmentioning
confidence: 99%